“Fatal betrayal”of the Church: the question of “ecclesiastical bolshevism” at the Local Council of the Russian Orthodox Church (1917–1918) - Konstantin Kovyrzin (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The paper examines the phenomenon of “ecclesiastical Bolshevism”, i.e. a radical disruption of church order caused by the February Revolution of 1917. The term “ecclesiastical Bolshevism” refers to acts of insubordination of bishops, parish clergymen, monks and lay members of the Church to ecclesiastical authorities and their violating of canonical church discipline. The feature of the phenomenon was that the participants of inner church confl icts sought assistance from secular revolutionary authorities. The author points out the importance of documents from the Conference of Bishops and Judicial Commission of the Local Council of 1917–1918 for studying church confl icts on a diocesan scale. He analyses the activities of the special conciliar Commission designed to stop the disruptions of church order. The author concludes that the phenomenon of “ecclesiastical Bolshevism” was due to a number of reasons, the most important being the partial secularization of clergy and monastics and their loss of canon-law awareness. The external revolutionary factors became the catalyst for the critical tendencies already present in church life. The Local Council regarded “ecclesiastical Bolshevism” as a threat to the unity of the Church. The Episcopal Conference was considering the appeals of bishops deposed in the course of the “church revolution” from the very beginning of its work. The principal condemnation of “ecclesiastical Bolshevism” and the arrangements for countering it were defi ned in a special conciliar decree from April 6 (19), 1918.